Difficulties of differential diagnosis of botulism - G. A. Kharchenko; O. G. Kimirilova; A. A. Kimirilov (Лечащий Врач)
The article presents the differential diagnosis of botulism with the most significant diseases similar to botulism, based on the classic symptoms of botulism: the connection of the disease with food intake, the absence of fever, progressive muscle weakness, the presence of dry mouth, eye symptoms (blurred vision, diplopia, mydriasis, etc.), voice disorders (dysarthria), swallowing disorders (dysphagia).